(untitled) (Global Journal of Human-Social Science, 2018)
The main objective of the study was to find out the importance of mobilizing Wolaita community to participate in Wolaita language standardization issue. The research participants were purposively selected 22 individuals from Boditi town, Humbo wereda and two sectors from Wolaita zone level office. Questionnaire and in-depth interview were used as instruments for data collection. Both qualitative and quantitative data analysis methods were employed to find results. Hence, the findings showed that there were many significances of mobilizing the community to participate in Wolaita language standardization issue. The main importances were that the culture and language of Wolaita will develop, almost all people use similar and standardized language in all areas of Wolaita Zone. Transmitting mobilizing messages to the community through mass media like Wolaita FM radio 99.9 and affixing different placards were some of techniques to mobilize the people. Hence, it was recommended that the stake holders like Zone and wereda culture, tourism and government communication affairs department together with other government sectors should design possible strategies that enable them to mobilize the people to participate in Wolaita language standardization issue.